UTILIZATION OF MARICULTURE FISHERY RESOURCES IN AMBON BAY THROUGH GOVERNMENT POLICIES AND YOUTH INVOLVEMENT - Lekirupy, Ongen Rumaryo; Rahayu, Sri Panca (Aurelia Journal, 2025)
The utilization of mariculture fisheries resources in Ambon Bay faces several challenges, including technological limitations, limited market access, and suboptimal government policies. The Ambon City Government and the Maluku Provincial Government have designated this area for marine aquaculture development. Youth involvement is a crucial aspect, as young people serve as partners in the implementation of government policies. This study aims to identify the forms of youth involvement, government policies, and the utilization practices of mariculture fisheries resources in Ambon Bay. Data collection was conducted through interviews with 51 respondents. The identified forms of mariculture fisheries resource utilization include seaweed farming and fish cultivation using floating net cage systems. Youth involvement was categorized as follows: 5.9% as business owners, 68.6% as members of business groups, and 25.5% as laborers. Government policy interventions in the area include the provision of assistance or grants in the form of fish seed, feed, supporting facilities, and training by the Ministry of Marine Affairs and Fisheries, the Maluku Provincial Government, the Ambon City Government, as well as village and sub-district governments. These entities consistently provide support in the form of production facilities for fish farming using floating net cage systems. Government policies on youth empowerment need to be implemented comprehensively, beginning with the preparation of human resources (youth), the development of adequate competencies and skills, and the provision of accessible business capital. These efforts aim to encourage greater youth involvement in the utilization of mariculture fisheries resources in Ambon Bay.